COMMUNICATION STRATEGY FOR MEKAAR CUSTOMERS OF PT PERMODALAN NASIONAL MADANI SEMARANG - Hakim, Mohammad Rizal (jfpublisher, 2023)
Specialised financial institutions consisting of several institutions or companies established to fulfil specific tasks and functions, usually related to support government programmes for the community’s welfare. One of specialised financial institution is PT Permodalan Nasional Madani Semarang. It is a state-owned financial institution established as a commitment by the government to develop, promote and maintain MSMEs and Co-operatives. Therefore, this research aims to find out the effective method to overcome communication problems among customers due to the distinctiveness of Mekaar customers. The approach used is a descriptive qualitative approach which uses purposive sampling techniques combined with deductive data analysis. The results indicate that intents communication with customers regarding financing at Meekar co-operative is conducted to prevent defaults by customers in the future. In addition, assistance to customers must also be provided so that PT PNM policies can be implemented properly and customers are able to conduct non-cash transactions to reduce the risk of loss and so on.